Faktor-Faktor Yang Berhubungan Dengan Pemberian Susu Formula Pada Bayi 0-6 Bulan Di Puskesmas Tanoh Alas Kabupaten Aceh Tenggara Tahun 2023 - Rohana Fika SKD; Sri Rezeki; Damayanty S; Ade Rachmat Yudiyanto; Marta Armita Br Silaban (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Breastfeeding is the process of giving milk to babies or small children with breast milk (ASI) from the mother's breasts. Every effort is made to help mothers achieve success in breastfeeding their babies, which is called lactation management (Sutanto, 2018). Giving formula milk is not recommended for babies aged 0-6 months, because it can increase the risk of illness and even death in babies. UNCIEF states that giving formula milk can increase by 25 times the incidence of death in babies early in life compared to babies who are given exclusive breast milk. This study used an analytical research design with a cross-sectional study approach, the population in the study was 50 people using Consecutive Sampling sampling, all subjects who came and met the selection criteria, and were included in the study until the required number of subjects was met. The data analysis used is chi square. The results of statistical tests using the Chi Square test obtained a result of 0.004. These results are smaller than the P value (0.05) or 0.004<0.05, meaning that there is a significant relationship between maternal knowledge and formula milk feeding, so the hypothesis in this study can be accepted. The results of statistical tests using the Chi Square test obtained a result of 0.003. These results are smaller than the P value (0.05) or 0.003<0.05, meaning that there is a significant relationship between maternal education and formula milk feeding, so the hypothesis in this study can be accepted. The results of statistical tests using the Chi Square test obtained a result of 0.005. These results are smaller than the P value (0.05) or 0.005 < 0.05, meaning that there is a significant relationship between mother's work and giving formula milk, so the hypothesis in this study can be accepted. The conclusion is that there is a relationship between maternal education and the provision of formula milk at the Tanoh Alas health center. It is hoped that this research can be used to provide appropriate steps or strategies to encourage the public and health workers to provide exclusive breastfeeding, by minimizing the factors that influence early provision of formula milk.